Los canales virtuales, una opción para fortalecer las organizaciones financieras solidarias - Andrade Merino, Raúl Vicente; Dillon Gallegos, Juan Francisco; Andrade Romero, Mauro Patricio; Andrade Montalvo, Felipe (mktDESCUBRE11, 2018)
We conducted a study on the strategies that can be used by solidarity financial organizations in virtual channels, to boost their management in favor of the non-formal sector of the economy. Virtual communication has become, in a system used for all kinds of people, to interrelate, consolidate their personal relationships, search for goods and services, carry out financial, commercial transactions, that is, use them to carry out all the activities required by the 21st century. . Organizations will also benefit from virtual communications, to expand their markets, research, promote and sell their products and services, organize their commercial and financial operations, guide tastes and preferences, register their organizational obligations with their staff and business stakeholders, streamline financial transactions using the future time by the veracity and speed of the financial financial that benefit those who participate in its virtual characteristics. The solidarity financial organizations, the electronic accounts, the electronic transfers, the electronic accounts, the electronic accounts, the electronic payments, the virtual credit management, the offer of products and services to their associates, management of their daily operations, these benefits have the efficiency of associative organizations is optimized. Through the exploratory, descriptive and logical inductive method we determine all these characteristics.